THE INNER CONFLICTS OF FEMALE CHARACTERS IN THE NOVEL AYAT-AYAT CINTA2 BY HABIBURRAHMAN EL SHIRAZY (LITERARY PSYCHOANALYTIC APPROACH) - Zamil, Muzzamilah; Zuriyati, Zuriyati (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The purpose of this study is to gain a deep understanding about the inner conflicts of female characters with the approach of literary psychoanalysis. This research uses content analysis method with qualitative approach. The results showed that of all characters experiencing inner conflicts, the character of Sabina the most dominant experiencing of inner conflicts. While the most dominant form of inner conflict occurs it is an approach-avoidance conflict. It can be seen that a form of the approach-approach inner conflicts there are 2.78% of data, form of approaching - avoidance inner conflict there are 83.33% of data. Furthermore, the avoidance-avoidance inner conflict there are 13.89% of data. Based on these findings, the results of this study can be implicated into Indonesian language and literature learning at the SMA / MA level.